Pendidikan Anak Usia Dini Berbasis Komunitas di Desa Lasitae: Model Pemberdayaan Melalui Pendekatan Participatory Action Research (PAR) - Arsyad Genda; Musrayani Usman; Andi Muhammad Arif Haris; Mario Mario; Andi Anggraini Marabintan; Sahrul Ramadhan; Andi Fadilah Aryani; Askar Askar (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This community service activity aimed to enhance the capacity of local cadres and parents in community-based early childhood education (PAUD) in Lasitae Village, Barru Regency, South Sulawesi. The program was implemented through a Participatory Action Research (PAR) approach, which actively involved coastal communities in planning, training, mentoring, and evaluation. The pre–post test results showed a significant increase in knowledge (55.4→81.5; +46.9%), skills (57.8→84.3; +45.8%), and participatory attitudes (62.3→82.3; +32.0%). Community engagement also rose from an average of 35.4% to 79.0%, marked by the establishment of the local initiative “Kelas Cerita Bahari” (Maritime Story Class) and active collaboration among cadres, teachers, and parents. Learning products such as the storybook Ikan Parappo dan Ombak Ramah (“Parappo Fish and the Friendly Waves”) and the song Marennu’ Ri Lautta (“Joy of the Sea”) strengthened the integration of maritime cultural values into the PAUD curriculum. These results demonstrate that community-based education and the funds of knowledge approach effectively build critical awareness, strengthen social capital, and promote sustainable early childhood education rooted in local culture. The program recommends replicating this model in other coastal villages to strengthen a participatory and socially just education ecosystem.